Continuing professional development (CPD) for junior high school mathematics teachers: An evaluation study - Pika Merliza; Heri Retnawati (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2018)
Responding to the importance of conducting evaluation on continuing professional development program for teachers, this study is aimed at describing the implementation and difficulty of Continuing Professional Development (CPD) of mathematics teachers of Junior High School (JHS) in Bandar Lampung, Indonesia. This research used a descriptive approach employing a quantitative-qualitative method with sequential explanatory strategy. The population of the research was 181 junior high school mathematics teachers who have already become civil servants. The samples were 63 teachers for quantitative research selected using stratified random sampling and proportional random sampling technique, while eight teachers for qualitative research were selected using purposive sampling technique. These eight teachers were selected because they were the only teachers handling the CPD program. The data were collected through a test, questionnaires, checklist sheet, study document, and interview. Data analysis was conducted using categorized performance trends, divided into five groups: Very Good/Difficult, Good/Difficult, Fair, Poor/Easy, and Very Poor/Very Easy. The data were analyzed using descriptive technique; the quantitative study analysis was performed by mean and standard deviation, whereas, the qualitative data analysis was obtained by data reduction, data display, and conclusion technique. The research results show that the majority of teachers’ CPD implementation is very poor, meanwhile, the difficulty of the engagement of CPD is categorized as fairly difficult.